Studi Keanekaragaman Vegetasi Rumput Dan Herba Di Hutan Sekipan Desa Kalisoro Tawangmangu Karanganyar Provinsi Jawa Tengah - Utami, Danik Tri Wahyu; , Efri Roziaty, S.Si. M.Si (2017)
Sekipan Forest Tawangmangu Karanganyar is a forest that has high biodiversity. Vegetation of grasses and herbaceous are plant communities that make up stratification near to ground. The purpose of this research is to know the taxonomy of species and index of diversity of grass and herbaceous vegetation types found in Sekipan Forest Tawangmangu Karanganyar. This method used purposive random sampling method with 10 plot of each plot measuring 1 m x 1 m within 5 - 10 m. The results of the research showed that the grass vegetation level consisted of 2 orders 2 families 8 genus 8 species, while herbaceous vegetation consisted of 10 orders 11 families 11 genus 11 species. Total number of all individuals is 268 individuals scattered at an altitude of 1200 m.dpl, 1.250m.dpl and 1300 m.dpl in the Sekipan Forest Tawangmangu Karanganyar. Vegetation of grasses and herbs which has the highest important value index is Garden Balsam Seed (Impatiens balsamina L.) 0.0371 and lowest is Mimosa flower (Mimosa pudica L.) 0,0027. The highest diversity index is elephant grass/ naper grass (Axonopus compressus) 0.10832 and the lowest Mimosa flower (Mimosa pudica L.) 0,00899. The diversity of grass and herbaceous vegetation in Tawangmangu Karanganyar Sekipan Forest is low one. Keywords: Vegetation of grasses and herbaceous, Diversity Index, Sekipan Forest.